Development of offshore outsourcing industry and its influences on training and development- exploring China and Malaysia's experience - Chong, Soon Meng * (2011)
It cannot be denied that for the past 3 years since China made its first foray to invite FDI in 1979, the country?s economy has been progressing at a rapid pace. Technical and education advancement have contributed to the nation?s ability to position itself as an important offshore outsourcing destination for the world. At the same time, this industry also contributes to the nation?s economic growth. As at June 2009, China has close to 7000 enterprises focusing on offshore industry. Data shows that this particular sector has provided employment to at least 1.2 million Chinese people. This seems to be similar in Malaysia?s situation where Malaysia too, has begun to offer and further develop this service as it is a key contributor to the country?s GDP. In fact, according to the A. T. Kearney Global Services Location Index of March 2011, China and Malaysia were ranked in the top three offshoring? outsourcing countries in the world. Despite China?s success in the outsourcing industry, many global companies are still experiencing challenges to attract and retain talent in China. The paper examines the skill shortage in China?s offshoring and outsourcing industry and provides insight into Malaysia?s experience with the Human Resources Development Fund on developing its workforce. The paper will also provide some suggestions on the various institutional and policies levers that could address the skills shortage challenges in China.